2016
DOI: 10.1111/inm.12247
|View full text |Cite
|
Sign up to set email alerts
|

Influencing and protective factors of suicidal ideation among older adults

Abstract: Suicide is a global issue, but few studies have explored the triggers and psychological feelings of suicidal ideation in older adults. A qualitative design with face-to-face semistructured interviews examined the experience of suicidal ideation in adults aged 65 years and older. A purposive sampling of 32 outpatients with suicidal ideation from a medical centre in northern Taiwan participated. Interview data identified three themes: triggers for suicidal ideation, contributing psychological changes, and factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
3

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 21 publications
1
26
0
3
Order By: Relevance
“…Additionally, the experience of neglect from family members or caregivers and social isolation may make them suffer due to a lack of social belonging. These results are consistent with previous studies in which depression and thwarted belongingness are the main predictors of suicidal ideation [16,23,33,34].…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, the experience of neglect from family members or caregivers and social isolation may make them suffer due to a lack of social belonging. These results are consistent with previous studies in which depression and thwarted belongingness are the main predictors of suicidal ideation [16,23,33,34].…”
Section: Discussionsupporting
confidence: 93%
“…También se aplica a un amigo cercano que puede proporcionar apoyo emocional para que los clientes se sientan escuchados y atendidos. Esta forma de conciencia ayuda al cliente a poder ver su mundo positivo para que pueda reducir los pensamientos de suicidio (14) .…”
Section: También Le Dan Trabajo Para Arreglar La Pared Creando Jauunclassified
“…Cuatro de seis clientes de intento de suicidio tenían un diagnóstico médico de depresión severa. De acuerdo con la investigación que dice que aproximadamente el 60% del riesgo de suicidio del cliente informó haber experimentado ansiedad, depresión o una combinación de ambos (14) . También se obtuvieron declaraciones de respaldo de los resultados de un estudio que informó que los pacientes con depresión tenían 7 veces más probabilidades de morir por suicidio.…”
Section: Convulsión Y Luego Llevado Al Hospital" (P6)unclassified
See 1 more Smart Citation
“…On the other hand, in a thesis, it stated that pre-service teachers have varying levels of knowledge about mental illness (Conroy, 2020). To further support this claim, a group of researchers indicated that the triggers for suicidal ideation for adults were physical discomfort, loss of respect and/or support from family, impulsivity due to conflicts, and painful memories (Huang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%